3D reconstruction of the Lapis Tiburtinus (Tivoli, Central Italy): The control of climatic and sea‐level changes on travertine deposition. (12th June 2021) - Mancini, Alessandro; Della Porta, Giovanna; Swennen, Rudy; Capezzuoli, Enrico
Abstract: 3D modelling is a fundamental tool to visualize and understand the history of sedimentary basin filling and to reconstruct the geobody architecture. Spatial distribution of discontinuity surfaces and geobody characteristics provide valuable information on the factors controlling the sedimentary evolution of basins. Several Neogene‐Quaternary basins of central‐western Italy are controlled by extensional and strike‐slip tectonics and characterized by travertine deposition, related to hydrothermal fluids rising up along discontinuities and fractured carbonate bedrocks. This study presents the 3D modelling results of the quarry area within the tectonically controlled Acque Albule Basin (Tivoli, Central Italy) that hosts the Pleistocene Lapis Tiburtinus travertine. The 3D reconstruction of the different surfaces bounding the travertine units shows a complex architecture composed of depressions, reliefs and channels as predominant morphological elements related to four different depositional environments (subaqueous, palustrine, slope and travertine channel). The reconstructed surface maps highlight the presence of laterally migrating, E–W‐oriented lens‐shaped geometries, with a drainage system persistent through time oriented towards the southern part of the study area in the direction of the Aniene River, bordering the Acque Albule Basin in the South. The Lapis Tiburtinus travertine developed in an area of 28 km 2, accumulated in a system composed of sub‐basins (approximately 1–2 km 2 wide) with subaqueous conditions interconnected by a hydrographic network, controlled through time by fluctuations of the Aniene River base level. Based on the results obtained, base‐level fluctuations of the Aniene River, related to glacio‐eustatic sea‐level oscillations of the last 115 kyrs associated with alternation of humid and arid climatic conditions, arise as the most important factor affecting the architecture of the travertine geobodies. Abstract : The Lapis Tiburtinus travertine developed in a system of sub‐basins with subaqueous conditions interconnected by a hydrographic network controlled through time by fluctuations of the Aniene River base level